Exploration of Indonesian Plants as Skin Lightening against Tyrosinase: A Virtual Screening - Pandu Hariyono; Jasson Rhinehard Karamoy; Maywan Hariono (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Aesthetic is nowadays becoming as one of the important things for people to increase self-confidence. Flawless skin could be one of the desired looks especially for females which is a valuable cosmetics market. Skin browning is often associated with dermatological problems which may lead to hyperpigmentation due to the increase of the melanin biosynthesis. Skin browning could be caused by the overproduction of melanin which is accelerated by the presence of human tyrosinase. Therefore, the inhibition of this kind of enzyme is associated with skin lightening. In this present study, we perform in silico virtual screening against human tyrosinase by utilizing a natural product database from Indonesia Herbal Database (http://herbaldb.farmasi.ui.ac.id/v3/) to select 20 hit compounds. The simulation was carried using AutoDock Vina via molecular docking. The result shows that from 200 compounds of the database, those hits have a free energy of binding range from -12.1 to -9.2 kcal/mol predicting the affinity of the corresponding compounds towards human tyrosinase associating with its potential as a skin whitening agent. The hits correspond to their presence in Indonesian local plant that could be potential as resources for skin whitening.Keywords: Indonesian plant, molecular docking, skin lightening, tyrosinase, virtual screening.